Anxiety, Depression, and Pain Symptoms: Associations With the Course of Marijuana Use and Drug Use Consequences Among Urban Primary Care Patients. Issue 1 (January 2018) - Bertholet, Nicolas; Cheng, Debbie M.; Palfai, Tibor P.; Lloyd-Travaglini, Christine; Samet, Jeffrey H.; Saitz, Richard
Abstract : Objectives: This exploratory study aims to investigate whether anxiety, depression, and pain are associated with changes in marijuana use and drug use consequences among primary care patients. Methods: In all, 331 adult primary care patients with marijuana as the only drug used were followed prospectively to investigate associations between anxiety/depression symptoms (no/minimal symptoms; anxiety or depression symptoms; symptoms of both) and pain (1–10 scale: none [0]; low [1–3]; medium [4–6]; high [7–10]) (independent variables) and substance use outcomes in regression models. These outcomes were changes (over 6 months) in primary outcomes: marijuana use days (past 30); and drug use consequences (Short Inventory of Problems—Drugs [SIP-D]); secondary outcomes—drug use risk (Alcohol, Smoking, and Substance Involvement Screening Test [ASSIST] score for drugs). Results: At baseline, 67% reported no/minimal anxiety/depression symptoms, 16% anxiety or depression symptoms, 17% both; 14% reported no pain, 16% low, 23% medium, 47% high pain level. Mean (SD) number of marijuana use days was 16.4 (11.6), mean SIP-D 5.9 (9.0), mean ASSIST 12.5 (7.8); no significant association was found between anxiety/depression and marijuana use changes. Given the same baseline status for SIP-D and ASSIST, respectively, those with anxiety or depression had greater increases in SIP-D (adjusted mean difference [95% confidence interval] +3.26 [1.20; 5.32], P  = 0.004) and borderline significant increases in ASSIST (+3.27 [−0.12; 6.65], P  = 0.06) compared with those without anxiety or depression; those with both anxiety and depression had greater increases in ASSIST (+5.42 [2.05; 8.79], P  = 0.003), but not SIP-D (+1.80 [−0.46; 4.06], P  = 0.12). There was no significant association between pain and marijuana use and SIP-D changes. Given the same baseline ASSIST level, those with high pain level had greater increases in ASSIST (+4.89 [1.05; 8.72], P  = 0.04) compared with those with no pain. Conclusion: In these exploratory analyses, anxiety, depression, and high pain level appear to be associated with increases in drug-related harm among primary care patients using marijuana.